The Financing of Startups in Poland and The EU - Selected Issues - Pawel PERZ (Communications of International Proceedings, 2023)
Startups are firms with a short history of operation that try to commercialize innovative ideas. They always have innovative products or services and/or new business models. Startup companies are considered as an important player in economic development and job creation. In the case of market success, they are able to grow very quickly and become large organizations, however, their activities in the early phase are characterized by high risk. Due to this, they require special financing methods. The article characterizes and compares the most important sources of financing for startups in the European Union and Poland. The attention was paid to the role of financing in creating conditions for the development of such enterprises.
Keywords: startups; financing; sources of financing (JEL: M13)